The MentalPlus® Digital Game Might Be an Accessible Open Source Tool to Evaluate Cognitive Dysfunction in Heart Failure with Preserved Ejection Fraction in Hypertensive Patients: A Pilot Exploratory Study - Valeria Fontenelle Angelim Pereira; Livia Stocco Sanches Valentin (International Journal of Hypertension)
Introduction. Cognitive dysfunction with heart failure with reduced ejection fraction (HFrEF) is well studied. However, there are few comparative studies with heart failure and preserved ejection fraction (HFpEF). Cognitive dysfunction diagnosis usually demands a long neuropsychological battery. We developed MentalPlus® digital game to overwhelm that issue. Methods. As a pilot study, we evaluated 60 patients with systemic hypertension and HFpEF. They were submitted to TICS (Telephone Interview Cognitive Status) to evaluate the general cognitive function and 25 minutes of MentalPlus® digital game evaluation. Results. The results disclosed 60 hypertensive patients. All of them presented with HFpEF. Patients presented a mean age of 56±10 years; 46% male; LVMi (g/m2) mean of 110±20; educational attainment of 9 years or more; mean income of 8 Brazilian minimum wages. The TICS results disclosed 28 ±3.7. MentalPlus® digital game evaluation disclosed preserved values for the phases I, III, IV, V, VI, and VII. Phase II, short-term memory related, was below the normals values that were assigned. This group of patients presented a normal general cognition by both evaluations, except for specific functions displayed above, disclosed by MentalPlus®. The MentalPlus® was designed to possibly evaluate specific cognitive functions separately, like attention, memory, executive function, and language, because each phase evaluates specific functions shortly. Conclusion. Hypertensive HFpEF patients presented in general a normal cognition, except for some aspects related to short-term memory. The MentalPlus® digital game, compared with TICS, presented similar general results. It is an advantage that MentalPlus® software could be used to assess cognitive function, in general and individually, and be an open tool shortly.